A study of spatial price efficiency of food grain marketing in northeastern Nigeria - Nuhu, H.S.; Amaza, P.; Gaya, H. (2007)
The study examined spatial aspects of marketing efficiency in urban marketing system for maize, sorghum and cowpea in north eastern Nigeria. The data for the study were obtained from both secondary and primary sources. Primary data was obtained through the use of structured questionnaires, interviews and market surveys on transportation/handling cost. Four markets (Maiduguri, Damaturu, Gombe and Yola) known for marketing of cereal grains and pulses were selected purposely for the study.